Analisis Faktor Risiko Perdarahan Antepartum pada Ibu Hamil dengan Plasenta Previa di RSUD X - Fauziah, Ayu Bella; Rahmat, Rezqiqah Aulia (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Placenta previa is a major cause of antepartum hemorrhage, which can increase maternal and perinatal morbidity and mortality. Identifying risk factors is crucial for optimal prevention and management. Objective: To analyze the risk factors associated with antepartum hemorrhage in pregnant women with placenta previa at RSUD X. Methods: This study used a quantitative, analytical, observational design with a retrospective approach. The sample consisted of pregnant women diagnosed with placenta previa who were treated at RSUD X between January 2020 and December 2024. Data were collected through medical records and analyzed using the chi-square test. Results: Of the 82 respondents, 56 (68.3%) experienced antepartum hemorrhage. Significant risk factors included parity ≥3 (p=0.015), history of previous cesarean section (p=0.004), and maternal age >35 years (p=0.039). Non-significant factors included pregnancy spacing and history of abortion. Conclusion: High parity, advanced maternal age, and a history of cesarean delivery significantly contribute to the increased risk of antepartum hemorrhage in placenta previa.